Amine‐bridged bis(phenol) ligands for efficient Pd‐catalyzed aqueous C‐C coupling reactions. (27th August 2013) - Zhou, Zhonggao; Liu, Minyan; Wu, Xiaoli; Yu, Hongwei; Xu, Guohai; Xie, Yongrong
<x xml:space="preserve">Abstract</x> The influence of ring size (5 or 6), chain length (1, 2 or 3) and bulkiness of N‐aryl substituents in amine‐bridged bis(phenol) ligands (1, 2, 3) on palladium‐catalyzed aqueous C‐C coupling reactions were revealed. The homocoupling of arylboronic acid can be completed in neat water with the aid of a catalytic amount of p‐toluenesulfonyl chloride (TsCl) in a very short time under anaerobic or aerobic conditions. Interestingly, the same catalytic system was efficient for Suzuki–Miyaura reaction in aqueous acetone under aerobic conditions in the absence of TsCl. The crystal structures of ligand 1 and three unsymmetrical fluorine‐substituted biaryl derivatives were also reported. Copyright © 2013 John Wiley & Sons, Ltd.